A Study on Suicide among Youth – Epidemiology, Potential, and Treatment: Understanding the complexities and implications of adolescent suicide (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Suicide is a major death factor and a complicated psychiatric consequence. In this essay, we review the latest state of study in the field of adolescent suicide. We are looking at their definitions maturations and phenomenologist, epidemiology, theoretical etiological and psychological processes. There is a lot to do to enhance the awareness of adolescent suicide ideas and behavior.